Manifestasi Filsafat Nilai Dalam Pendidikan Islam - Sultani Sultani; Khojir Khojir (Al-Riwayah : Jurnal Kependidikan, 2023)
Education is a tool for helping each person reach their full potential as a valuable, admirable person. Human characteristics result from values that allow for the precedence of thoughts, words, and deeds. This study aims to outline the value philosophy and how it appears in Islamic education. A qualitative approach to library research was used for this study. Measure the truthfulness of messages and derive conclusions using content analysis techniques used in data processing and analysis. According to the study's findings, value is etymologically related to price and estimated numbers of significant attributes that are beneficial to many individuals. However, values are criteria that exist in humans in the forms of good, just, and beautiful from a philosophical perspective. The Islamic notion of moral education is consistent with the theory of value in the philosophy of value, which has as its goal the revelation of good and true character. Islamic education, on the other hand, aims to delve into the nature of virtue and truth. Philosophers believe that human beings are defined as beings of value or quality because of how they grasp and apply the essence of goodness and truth